Effectiveness of various interventions for non-traumatic osteonecrosis: a pairwise and network meta-analysis - Zhai, Shaoyang; Wu, Rui; Zhao, Jie; Huang, Wang; Hu, Weiwei; Huang, Weichen (Frontiers in Endocrinology, 2024)
Background Osteonecrosis of the femoral head (ONFH) is acknowledged as a prevalent, challenging orthopedic condition for patients. Purpose This study aimed to evaluate the efficacy of various interventions for non-traumatic ONFH and provide guidance for clinical decision-makers. Methods We searched PubMed, Embase, Cochrane Library, and Web of Science databases from inception to February 2023 for relevant randomized controlled trials evaluating treatments for femoral head necrosis, without language restrictions. Quality evaluation was performed using the Cochrane risk-of-bias assessment tool, and analysis was performed using Stata 15.1. Results Eleven randomized controlled trials were included in this study. The meta-analysis results revealed that CellTherapy [MD= -3.46, 95%CI= (-5.06, -1.85)], InjectableMed [MD= -3.68, 95%CI= (-6.11, -1.21)], ESWT [MD= -2.84, 95%CI= (-4.23, -1.45)], ESWT+InjectableMed [MD= -3.86, 95%CI= (-6.22, -1.53)] were significantly more effective in improving VAS pain score than CD+PTRI, as well as CD+BG+CellTherapy, and CD+BG. Furthermore, CD+BG+CellTherapy was better than CD+BG [MD= -0.97, 95%CI= (-1.71, -0.19)]. The SUCRA ranking for HHS score indicated that CellTherapy (77%) has the best effectiveness rate, followed by ESWT+InjectableMed (72.2%), ESWT (58.3%), InjectableMed (50%), CD+PTRI (31.4%), and CD+BG (11%). In terms of WOMAC and Lequesne scores, the meta-analysis showed no statistically significant differences between the experimental group CD+BG+CellTherapy and the control group CD+BG. Conclusions CellTherapy and non-surgical ESWT combined with medication or CellTherapy have the best effect on ONFH. Surgical CD+BG combined with CellTherapy is more effective than CD+BG alone. ESWT+InjectableMed is recommended for short-term or acute onset patients, while ESWT is recommended for long-term patients.